2014
DOI: 10.1104/pp.113.232314
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Auxin Signaling Pathways Respond to High-Temperature Stress during Anther Development as Revealed by Transcript Profiling Analysis in Cotton  

Abstract: Male reproduction in flowering plants is highly sensitive to high temperature (HT). To investigate molecular mechanisms of the response of cotton (Gossypium hirsutum) anthers to HT, a relatively complete comparative transcriptome analysis was performed during anther development of cotton lines 84021 and H05 under normal temperature and HT conditions. In total, 4,599 differentially expressed genes were screened; the differentially expressed genes were mainly related to epigenetic modifications, carbohydrate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(213 citation statements)
references
References 56 publications
7
204
1
1
Order By: Relevance
“…Microscopic confirmation of abortion at this stage following exposure to temperatures ≥30 • C has been reported for cereal and eudicot crops to include rice ( Fig. 3D; Bagha, 2014), wheat (Saini and Aspinall, 1982;Saini et al, 1984), sorghum (Jain et al, 2007), barley (Sakata et al, 2000;Oshino et al, 2007), snap beans (Suzuki et al, 2001), cowpea (Ahmed et al, 1992), tomato (Iwahori, 1965), Brachypodium distachyon (Harsant et al, 2013), cotton (Min et al, 2014), and garlic (Mayer et al, 2015). The uninucleate stage is more sensitive in the low 30 • C range in cool-season crops such as barley, wheat, and garlic whereas temperatures in the mid-to-upper 30 • C range effect development in warm-season crops.…”
Section: High Temperature and Uninucleate Microspore Developmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Microscopic confirmation of abortion at this stage following exposure to temperatures ≥30 • C has been reported for cereal and eudicot crops to include rice ( Fig. 3D; Bagha, 2014), wheat (Saini and Aspinall, 1982;Saini et al, 1984), sorghum (Jain et al, 2007), barley (Sakata et al, 2000;Oshino et al, 2007), snap beans (Suzuki et al, 2001), cowpea (Ahmed et al, 1992), tomato (Iwahori, 1965), Brachypodium distachyon (Harsant et al, 2013), cotton (Min et al, 2014), and garlic (Mayer et al, 2015). The uninucleate stage is more sensitive in the low 30 • C range in cool-season crops such as barley, wheat, and garlic whereas temperatures in the mid-to-upper 30 • C range effect development in warm-season crops.…”
Section: High Temperature and Uninucleate Microspore Developmentmentioning
confidence: 90%
“…The negative impact of HT and other stresses on the timing of tapetal cell death and tapetal invertase activity is proposed to limit provisioning of compounds, to include hexose, to developing pollen and it has been hypothesized that this results in microspore starvation and subsequently, abortion (Parish et al, 2012;De Storme and Geelen, 2014). Mistimed tapetum programmed cell death or downregulation of invertase genes are not universally associated with abortion of uninucleate microspores at HT (Endo et al, 2009;Bagha, 2014;Min et al, 2014). Alterations in tapetal death and carbohydrate metabolism in anthers following exposure to HT, to include invertase activity in some species, may be only part of a complex response wherein a network that normally senses elevated temperatures and re-establishes cellular homeostasis subsequently fails.…”
Section: High Temperature and Uninucleate Microspore Developmentmentioning
confidence: 98%
“…This, together with recent progress on the roles of sugars in auxin biosynthesis and signaling (Wang and Ruan, 2013), prompted us to investigate the expression of auxin-related genes in 21-d stamen. Several stamen-expressed candidate genes involved in auxin biosynthesis, transport, and perception were chosen to measure their mRNA levels, based on previous studies (Min et al, 2014). Most notably, the transcripts of two auxin biosynthesis genes, GhTAA1 and GhYUC5, were reduced significantly in the RNAi stamen (Fig.…”
Section: Rnai-mediated Suppression Of Ghvin Expression Led To a Signimentioning
confidence: 99%
“…For example, heat-stressed cotton plants also exhibit abnormal stigma protrusion, delayed anther dehiscence, and reduced pollen viability (Brown, 2001;Snider et al, 2009;Min et al, 2014) as well as high rates of boll shedding and seed abortion (Powell, 1969;Reddy et al, 1992;Brown, 2001). Min et al (2014) also reported that the impaired anther and pollen development under high temperature were associated with reduced expression of INV and starch synthesis genes, decreased Glc level, as well as disrupted auxin biosynthesis. Similarly, wheat male reproductive failure under water deficit was related to decreased VIN (Ivr5) and CWIN (Ivr1) gene expression in pollen (Koonjul et al, 2005).…”
Section: Vin Along With Cwin Could Act As a Gatekeeper For Reproducmentioning
confidence: 99%
“…To evaluate the potential production of EC, cotton explants that were transformed with 35S::GUS, 35S: GhCKI, and 35S:iGhCKIv, callus of transgenic Arabidopsis plants, and mutant lines from different culture times were imaged using a Nikon D40 Camera. The cotton explants were sectioned into 8-mm-thick slices with a microtome, stained with 0.1% aniline blue, and observed according to the work by Min et al (2014). Electronic microscopic analyses (TEM) of the callus were conducted as previously described (Min et al, 2013).…”
Section: Gus Activity and Histochemical And Microscopic Analysesmentioning
confidence: 99%